2013
DOI: 10.1016/j.jmps.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the pressure–volume curve of an elastic microsphere composite

Abstract: The effective macroscopic response of nonlinear elastomeric inhomogeneous materials is of great interest in many applications including nonlinear composite materials and soft biological tissues. The interest of the present work is associated with a microsphere composite material, which is modelled as a matrix-inclusion composite. The matrix phase is a homogeneous isotropic nonlinear rubber-like material and the inclusion phase is more complex, consisting of a distribution of sizes of stiff thin spherical shell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Although inhomogeneous, the purely radial nonlinear elastic deformation associated with the inflation and deflation of an incompressible hollow sphere subjected to hydrostatic pressure is a universal solution belonging to 'Family 4' (see [58,59]). The problem is straightforward and its solution has long been known (see, for example, [28,58] and references therein). The equilibrium equation can be integrated exactly to yield a nonlinear equation for the internal deformed void radius a (or equivalently for the external radius b) in terms of the imposed pressure difference and the undeformed radius A (or the external undeformed radius B, respectively), in the form…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inhomogeneous, the purely radial nonlinear elastic deformation associated with the inflation and deflation of an incompressible hollow sphere subjected to hydrostatic pressure is a universal solution belonging to 'Family 4' (see [58,59]). The problem is straightforward and its solution has long been known (see, for example, [28,58] and references therein). The equilibrium equation can be integrated exactly to yield a nonlinear equation for the internal deformed void radius a (or equivalently for the external radius b) in terms of the imposed pressure difference and the undeformed radius A (or the external undeformed radius B, respectively), in the form…”
Section: Introductionmentioning
confidence: 99%
“…B, b → ∞, on r = ∞) (figure 2). Given a strain energy function, the integral on the right-hand side in (1.1) is determined in a straightforward manner and the deformed radius a is determined numerically [28]. The corresponding linear viscoelasticity problem is also straightforward, and since the associated constitutive law in that case may be inverted without difficulty, both imposed displacement and pressure conditions can be derived.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies (Falou et al, 2010;Tu et al, 2009) have shown that the Poisson ratio of a typical ultrasound contrast agent is between 0.48 and 0.49 which is similar to rubber. The common approach to modelling rubber for moderate strains is to utilize nonlinear strain energy density functions which are either neo-Hookean or Mooney-Rivlin (De Pascalis et al, 2013). The key reason for introducing a compressible, third invariant is to account for the material parameter described by Poisson's ratio and to identify how this parameter influences the collapse time of the shell whereas a neo-Hookean or Mooney-Rivlin strain energy density function only utilizes the shear modulus (De Pascalis et al, 2013).…”
Section: Modelling the Quasistatic Stressing Of A Shelled Microbubblementioning
confidence: 99%
“…The common approach to modelling rubber for moderate strains is to utilize nonlinear strain energy density functions which are either neo-Hookean or Mooney-Rivlin (De Pascalis et al, 2013). The key reason for introducing a compressible, third invariant is to account for the material parameter described by Poisson's ratio and to identify how this parameter influences the collapse time of the shell whereas a neo-Hookean or Mooney-Rivlin strain energy density function only utilizes the shear modulus (De Pascalis et al, 2013). The compressible neo-Hookean strain energy density function is (Gorb & Walton, 2010)…”
Section: Modelling the Quasistatic Stressing Of A Shelled Microbubblementioning
confidence: 99%
“…De Pascalis et al. 18 have developed a mathematical model predicting the pressure/volume relationship of syntactic foam using Shorter’s work. He proposed the idea of modeling the compression as a two-step process: linear and non-linear, using the critical pressure defined by Fok and Allwright to set the transition between them.…”
Section: Introductionmentioning
confidence: 99%